Reverse-share-tenancy and Marshallian Inefficiency: Landowners’ bargaining power and sharecroppers’ productivity - Ghebru, Hosaena H.; Holden, Stein (International Food Policy Research Institute, 2013)
While there are ample empirical studies that claim the potential disincentive effects of sharecropping arrangements, the existing literature is shallow in explaining why share tenancy contracts are prevalent and diffusing in many developing countries. Using a unique tenant-landlord matched dataset from the Tigray region of Ethiopia, we are able to show how the tenants’ strategic response to the varying economic and tenure-security status of the landlords can explain sharecroppers’ productivity differentials.